Streamline characteristics using the computational fluid dynamic analysis in the flow of 18% EDTA irrigation solution to remove Ca(OH)2 - Anna Muryani; Hendra Dian Adhita Dharsono; Z. Zuleika; Ing. Mochammad Agoes Moelyadi; Diani Prisinda (Majalah Kedokteran Gigi Indonesia, 2018)
The remaining calcium hydroxide (Ca(OH)2) medicaments in the root canal wall can block the penetration of filling medicaments to the dentine tubule and cause the failure in the root canal treatment. One of the ways in cleaning the root canal wall from the remains of (Ca(OH)2) is by using 18% Ethylene Diamine Tetra Acetic Acid (EDTA) irrigation solution. The cleanliness of the root canal can be examined using the Computational Fluid Dynamics (CFD) analysis. The aim of this research was to see the description of the cleanliness of the root canal wall from the (Ca(OH)2) medicament with 18% EDTA irrigation by means of CFD analysis. This is a descriptive-explorative research. Having been validated with the experimental research using test specimen in the form of block resin made in accordance with the characteristics of root canal, the description of the cleanliness of the root canal wall from the (Ca(OH)2) medicament with the 18% EDTA irrigation was analyzed using CFD method. The irrigation needle used was the side-vented type with the position of 3 mm from the tooth apical. The results of the research showed the conformity between the result of experimental research and CFD research. One of the results of this research was the characteristics of streamline of 18% EDTA in the root canal showing a unique behavior due to the characteristics of the form of side vent irrigation needle. The irrigation flow in the coronal area of the inlet (side vent irrigation needle) showed a low velocity causing the more fluid flowing out from the inlet went to apical rather to the outlet (root canal orifice). In conclusion, this research showed that 18% EDTA solution indicated the conformity of validation results between experimental research and CFD research in the frames of 5, 10, 15, and 20 secs observed from experimental research with the of frame 0,010, 0,099, 0,150 and 0,410 secs as observed from CFD research.